The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/jacs.3c00282
|View full text |Cite
|
Sign up to set email alerts
|

Milestones and Most Recent Advances in Corrole’s Science and Technology

Abstract: The renaissance in corrole chemistry is strongly correlated with synthetic breakthroughs that started in 1999, regarding the one-pot rather than multistep syntheses of this heme-like N4 macrocycle. This largely improved synthetic accessibility allowed for technological advances wherein the corresponding metal complexes have since been introduced as key elements. Great emphasis was devoted to the elucidation of the unique fundamental features that distinguish corrole ligands, among them outstanding electron don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 165 publications
0
9
0
Order By: Relevance
“…With the concept of an “inverse hypercorrole” authenticated both experimentally and theoretically as a result of this work, there is clearly considerable room for creativity in the design of new anion chemosensors. In the same vein, biocompatible inverse hyperporphyrins and hypercorroles, on account of their NIR emission, may lend themselves to applications in photomedicine, as new dyes for photodynamic and photothermal therapies and as physiological oxygen sensors. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the concept of an “inverse hypercorrole” authenticated both experimentally and theoretically as a result of this work, there is clearly considerable room for creativity in the design of new anion chemosensors. In the same vein, biocompatible inverse hyperporphyrins and hypercorroles, on account of their NIR emission, may lend themselves to applications in photomedicine, as new dyes for photodynamic and photothermal therapies and as physiological oxygen sensors. , …”
Section: Discussionmentioning
confidence: 99%
“…In the early days of corrole chemistry, it was shown that simple corrole derivatives also conform to the four-orbital model . Soon, several cases of hypercorroles emerged, consisting of noninnocent transition metal meso -triarylcorroles in which the major optical transitions are thought to involve a significant degree of aryl-to-corrole charge transfer character. , Protonated meso -tris­( p -aminophenyl)­corrole, an analogue of [H 4 TAPP] 2+ , was also shown to exhibit a hyper spectrum .…”
Section: Introductionmentioning
confidence: 99%
“…One additional and less emphasized possible difference between corroles and porphyrins is the largest possible symmetry axis in the corresponding metal complexes, C 2 and C 4 , respectively. This affects not only spectroscopic features but also allows for selective substitution of the macrocyclic CH protons, as in the case of the 2,17-bis-sulfonated derivative which continues to be the most intensively studied corrole for medicinal applications. , An interesting hybrid case is presented by monoazaporphyrins (MAPs), with nitrogen instead of one meso -C-R position (R = H, alkyl, or aryl) of porphyrins since they have the coordination core of porphyrins and the symmetry of corroles (Scheme ). Synthesis of the first MAP was reported as early as 1936, followed by sporadic rational approaches for improving the synthetic accessibility of these macrocycles. Despite these reports, MAPs have been quite neglected in the field as compared not only to porphyrins, phthalocyanines, and the related tetraazaporphyrins but also relative to corroles.…”
Section: Introductionmentioning
confidence: 99%
“…Corroles are less explored in the areas of photonics and photocatalysis and have shown promising properties. Kar and co-workers developed NIR-emissive β-tetrathiocyano functionalized corrole-based dyes via a photocatalytic pathway in good yields. Our strategy is to synthesize a novel β-functionalized corrole with strong π-acceptor groups such as dicyanovinyl (DCV) and dicyanobutadienyl (DCBD), resulting in perturbation of the Soret and Q bands in the absorption spectrum. The recent literature on corroles revealed that π-extended corroles exhibit tunable photophysical and electrochemical redox properties. For example, copper corroles demonstrate hypercorrole spectra, and the Soret band contains more than one electronic transition with significant phenyl-Cu­(d x 2 –y 2 ) charge-transfer characteristics. , Gros et al have shown ligand-to-ligand charge transfer interactions in biscyano cobalt corroles to meso -NO 2 Ph groups .…”
Section: Introductionmentioning
confidence: 99%